Case report: clinical presentation and diagnostic findings in a cat with diabetes mellitus and hepatic-biliary disorders - Hafizsha, Nabila Latifa; Agung, Nabilah Putroe; Nurfadhilah, Elvina; Fitriana, Rizky (The Faculty of Veterinary Medicine of Syiah Kuala University, 2024)
Diabetes mellitus (DM) is a metabolic disorder and endocrinopathy characterized by hyperglycemia or a persistent increase in blood glucose levels. This case describes a male domestic cat exhibiting symptoms of vomiting, loss of appetite, and yellowish discoloration of the ears and oral mucosa, which was diagnosed with DM and hepatic-biliary disorders based on serum biochemistry and ultrasonographic examinations. The treatment included insulin injections, antibiotics, antiemetics, a liver supplement, and a specialized diabetic diet. After 14 days of insulin injection and a diabetic diet, the cats blood glucose levels returned to normal. A diabetic diet will be provided for the cat throughout its lifetime.